Danger or shelter? Lullabies in the music of Benjamin Britten - Leccia, M (Université de Bourgogne, 2023)
Britten’s playful aesthetic puts the child at the centre of many of his works. The lullaby is a genre which is therefore omnipresent. Through some case studies (A Charm of Lullabies, The Rape of Lucretia, The Turn of the Screw, A Midsummer Night’s Dream), this article considers the ways Britten tests the semiotic boundaries of the lullaby to create many ambiguous situations. With the transposition of a social and musical activity (to lull a child to sleep) on stage, Britten’s work blurs the mother-child relation by many inversions, and in particular makes of the child an ambivalent adult-like figure. The lullaby becomes paradoxically a protection and a luring danger. The article also reconsiders Britten’s own relation with his mother as well as it analyses the child-art and aesthetical implications of his juvenilia.